Total Variation Wavelet-Based Medical Image Denoising - Yang Wang; Haomin Zhou (International Journal of Biomedical Imaging)
We propose a denoising algorithm for medical images based on a combination of the total variation minimization scheme and the wavelet scheme. We show that our scheme offers effective noise removal in real noisy medical images while maintaining sharpness of objects. More importantly, this scheme allows us to implement an effective automatic stopping time criterion.